A Satirist of the Present, Chronicler of our Exile and a Visionary of the Possible - Thabo Tšehloane (The Thinker)
Morabo Morojele stands as a singular and resonant voice within the landscape of contemporary African literature. With only two novels—How We Buried Puso (2006) and Three Egg Dilemma (2023)—he has carved epochal milestones in the literary cartography of Southern Africa. These works do far more than chronicle the existential anxieties and social dislocations of their era; they radically reimagine the very possibilities of narrative form, language and the African novel itself.